Intervención del terapista respiratorio en paciente masculino de 54 años con edema agudo de pulmón. - Caicedo Medina, Joselyn Anais (2022)
Acute pulmonary edema corresponds to a pathology in which there is an abnormal accumulation in the alveolar spaces which are normally filled with air. This causes difficulty for the latter to perform an adequate gas exchange. The clinical case of a 54-year-old male with a history of type 5 kidney disease on dialysis is presented, who presented a day of evolution of dyspnea on medium efforts, diaphoresis, cough with expectoration and desaturation, which is progressive, for which he attends to the emergency unit of a nursing home. The objective of this clinical case study is to describe the intervention of the respiratory therapist in a 54-year-old male patient with acute pulmonary edema. Having as a conclusion that the actions of the respiratory therapy professional are of vital importance for the maintenance of adequate levels of arterial oxygenation which guarantee the functioning of the different organs of the body.